2019
DOI: 10.4143/crt.2018.537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platinum-Based Chemotherapy on PD-L1 Expression on Tumor Cells in Non-small Cell Lung Cancer

Abstract: Purpose Programmed death-1 (PD-1)/PD-1 ligand (PD-L1) axis blockades have revolutionized the treatment of advanced non-small cell lung cancer (NSCLC). We assessed the effect of platinum-based chemotherapy on tumor PD-L1 expression and its clinical implications. Materials and Methods We used immunohistochemistry to retrospectively evaluate the percentage of tumor cells with membranous PD-L1 staining (tumor proportion score) in paired tumor specimens obtained before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 31 publications
5
57
0
Order By: Relevance
“…A higher proportion of chemotherapy-treated patients in our study (48%) had a change in PD-L1 TPS, compared to other studies, showing changes in 3-41% of the patients [15][16][17][18][19][20]. The findings support the theory of possible chemotherapy-induced changes in the immune microenvironment and increment of tumor antigenicity, leading to changes in PD-L1 TPS [22].…”
Section: Changes In Pd-l1 From Baseline To Progression 621 Chemothsupporting
confidence: 76%
See 2 more Smart Citations
“…A higher proportion of chemotherapy-treated patients in our study (48%) had a change in PD-L1 TPS, compared to other studies, showing changes in 3-41% of the patients [15][16][17][18][19][20]. The findings support the theory of possible chemotherapy-induced changes in the immune microenvironment and increment of tumor antigenicity, leading to changes in PD-L1 TPS [22].…”
Section: Changes In Pd-l1 From Baseline To Progression 621 Chemothsupporting
confidence: 76%
“…The field of research in PD-L1 TPS changes in NSCLC is mainly dominated by retrospective studies including patients with localized/ resectable disease, having received neo-adjuvant or adjuvant chemotherapy [15][16][17][18][19][20][21]. To our knowledge, results from prospective studies are in general limited [14] and we have not been able to identify studies looking specifically at PD-L1 TPS changes.…”
Section: Changes In Pd-l1 From Baseline To Progression 621 Chemothmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Peng et al [55] supported this hypothesis by showing that, in ovarian cancer, paclitaxel can induce tumor cells to overexpress PD-L1 through the NF-κB pathway, thereby promoting the formation of a tumor immunosuppressive microenvironment. Shin et al [56] demonstrated that platinum-based chemotherapy can improve the expression level of PD-L1 in tumor cells of NSCLC patients. Thus, in this situation, blocking PD-L1 may achieve significant therapeutic effect, which explained why sequential therapy was still effective, while the addition of ipilimumab turned out to be invalid.…”
Section: Discussionmentioning
confidence: 99%
“…The case described in this report adds to the increasingly being of change in PD-L1 expression during therapy with either chemotherapy, targeted or immunotherapy [11][12][13][14]. Neoadjuvant chemotherapy may up-regulate the expression of PD-L1 in lung squamous cell carcinoma as was recently published [15].…”
Section: Discussionmentioning
confidence: 53%